2019
DOI: 10.1186/s13287-019-1448-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo conversion of rat astrocytes into neuronal cells through neural stem cells in injured spinal cord with a single zinc-finger transcription factor

Abstract: Background: Spinal cord injury (SCI) results in glial scar formation and irreversible neuronal loss, which finally leads to functional impairments and long-term disability. Our previous studies have demonstrated that the ectopic expression of Zfp521 reprograms fibroblasts and astrocytes into induced neural stem cells (iNSCs). However, it remains unclear whether treatment with Zfp521 also affects endogenous astrocytes, thus promoting further functional recovery following SCI. Methods: Rat astrocytes were transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…This reduction of the glial scar led to improved axonal regeneration and functional recovery (Rodriguez et al, 2014;Hesp et al, 2018;Zarei-Kheirabadi et al, 2019). These studies may provide us with clues as to how to manipulate the glial scar; that is, to reduce its density modestly without interrupting its integrity.…”
Section: Summary and Recommendations For Future Studymentioning
confidence: 95%
See 1 more Smart Citation
“…This reduction of the glial scar led to improved axonal regeneration and functional recovery (Rodriguez et al, 2014;Hesp et al, 2018;Zarei-Kheirabadi et al, 2019). These studies may provide us with clues as to how to manipulate the glial scar; that is, to reduce its density modestly without interrupting its integrity.…”
Section: Summary and Recommendations For Future Studymentioning
confidence: 95%
“…Since irreversible neuronal loss is another primary problem in SCI recovery, cell reprogramming may solve this problem by converting other cell types into neurons. Previous studies showed that in vivo, astrocytes can be reprogrammed into functional neurons after SCI through a single transcription factor (Su et al, 2014;Zarei-Kheirabadi et al, 2019). These reprogramming strategies exhibit limited efficiency in transforming astrocytes, thereby avoiding excessive attenuation of the glial scar.…”
Section: Direct Cell Reprogramming Strategiesmentioning
confidence: 99%
“…Several previous studies have resulted in a moderate glial scar reduction, intentionally or unintentionally, which leads to functional recovery. [42][43][44] These results may provide us with a new idea about how to manipulate the glial scar, which is to attenuate the density of the scar moderately without interrupting its integrity. In this study, we show that the Sox2-induced astrocytic reprogramming strategy can attenuate the density of glial scars more moderately, slowly, progressively, and partially and has higher clinical feasibility than the other interventions mentioned above.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, KLF4 might be a regulator of proliferation and migration in neurons, blood, kidneys, and skin cells 39 . Furthermore, Zarei‐Kheirabadi et al found that rat astrocytes were transdifferentiated into neural stem cells in vitro by ZFP521 or Sox2, and Wang et al confirmed that the p‐53 pathway could improve the reprogramming efficiency of the astrocytes to neuroblasts transition induced by Sox2 40,41 . In addition to these findings, the OCT4 and KLF4 TFs may be significant regulators of the biological behaviors of astrocytes by inducing cellular reprogramming.…”
Section: Discussionmentioning
confidence: 96%